The incidence of fatal breast cancer measures the increased effectiveness of therapy in women participating in mammography screening - Tabár L.; Dean P.B.; Chen T.H.-H.; Yen A.M.-F.; Chen S.L.-S.; Fann J.C.-Y.; Chiu S.Y.-H.; Ku M.M.-S.; Wu W.Y.-Y.; Hsu C.-Y.; Chen Y.-C.; Beckmann K.; et al. (John Wiley and Sons Inc., 2022)
Background: Women and their health care providers need a reliable answer to this important question: If a woman chooses to participate in regular mammography screening, then how much will this choice improve her chances of avoiding a death from breast cancer compared with women who choose not to participate?
Methods: To answer this question, we used comprehensive registries for population, screening history, breast cancer incidence, and disease‐specific death data in a defined population in Dalarna County, Sweden. The annual incidence of breast cancer was calculated along with the annual incidence of breast cancers that were fatal within 10 and within 11 to 20 years of diagnosis among women aged 40 to 69 years who either did or did not participate in mammography screening during a 39‐year period (1977‐2015). For an additional comparison, corresponding data are presented from 19 years of the prescreening period (1958‐1976). All patients received stage‐specific therapy according to the latest national guidelines, irrespective of the mode of detection.
Results: The benefit for women who chose to participate in an organized breast cancer screening program was a 60% lower risk of dying from breast cancer within 10 years after diagnosis (relative risk, 0.40; 95% confidence interval, 0.34‐0.48) and a 47% lower risk of dying from breast cancer within 20 years after diagnosis (relative risk, 0.53; 95% confidence interval, 0.44‐0.63) compared with the corresponding risks for nonparticipants.
Conclusions: Although all patients with breast cancer stand to benefit from advances in breast cancer therapy, the current results demonstrate that women who have participated in mammography screening obtain a significantly greater benefit from the therapy available at the time of diagnosis than do those who have not participated.